2013
DOI: 10.1186/1758-5996-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic analysis of human plasma reveals ether-linked lipids that are elevated in morbidly obese humans compared to lean

Abstract: BackgroundLipidomic analysis was performed to explore differences in lipid profiles between plasma from lean and obese subjects, followed by in vitro methods to examine a role for the identified lipids in endothelial cell pathophysiology.MethodsPlasma was collected from 15 morbidly obese and 13 control subjects. Lipids were extracted from plasma and analyzed using LC/MS, and MS/MS to characterize lipid profiles and identify lipids that are elevated in obese subjects compared to lean.ResultsOrthogonal partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 46 publications
(50 reference statements)
9
54
0
Order By: Relevance
“…This aligns with previous work by Fernández-Real et al ., which reported that FAs expressed as relative % values distinguished lean and obese individuals more strongly than when FAs were expressed as absolute values [12]. The outcome of our discriminant analysis modelling was also similar to that previously shown by Donovan et al, who reported a similar scatter plot distribution when using FA profiling to distinguish lean from morbidly obese individuals [41]. Of interest, it was noted that while the LH group in our study was clearly distinct from both of the obese groups, the classification of MHO and MUO individuals showed some overlap.…”
Section: Discussionsupporting
confidence: 89%
“…This aligns with previous work by Fernández-Real et al ., which reported that FAs expressed as relative % values distinguished lean and obese individuals more strongly than when FAs were expressed as absolute values [12]. The outcome of our discriminant analysis modelling was also similar to that previously shown by Donovan et al, who reported a similar scatter plot distribution when using FA profiling to distinguish lean from morbidly obese individuals [41]. Of interest, it was noted that while the LH group in our study was clearly distinct from both of the obese groups, the classification of MHO and MUO individuals showed some overlap.…”
Section: Discussionsupporting
confidence: 89%
“…This results from difficulties in determination of these compounds, associated either with their complex chemical characteristics or with the lack of appropriate instrumentation. Lipidomics is broadly defined as a structural and functional analysis of lipids and their metabolites .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, to simplify data processing, multivariate analysis techniques such as principal component analysis (PCA) and partial least squares of latent structures (PLS) have been used extensively in MS applications with the aim to find quantitative or qualitative differences between groups [1718]. …”
Section: Introductionmentioning
confidence: 99%